PARENTS' COMMUNICATION PATTERNS ON THE LEARNING BEHAVIOR OF CHILDREN AGED 7-12 YEARS DURING THE COVID-19 IN PURWOSARI VILLAGE, BANDAR DISTRICT - BENER MERIAH REGENCY - Ruhama Fitri; Samsul Bahri; Asmaul Husna; Fauziana Fauziana (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2021)
Every child has a different character, therefore communication patterns will result in learning behavior. This study aims to see how the communication patterns of parents to the behavior of children who learn 7-12 years during the COVID-19 period in Desa Purwosari, Kecamatan Bandar, Kabupaten Bener Meriah. This research is a qualitative research, descriptive method. The research subjects were 10 families of parents and children aged 7-12 years. The data technique uses observation, interview and documentation methods. Data analysis using data reduction, data presentation, and conclusion drawing. The results showed that in desa Purwosari, Kecamatan Bandar, Kabupaten Bener Meriah, parents used different communication patterns in accompanying children when learning, namely: permissive, authoritarian and democratic communication patterns. The pattern of communication frees parents to tend to ignore children when studying so that children's learning behavior is not directed and structured, children learn according to their own wishes, easily neglect their duties and obligations to study at home. Parents who use authoritarian communication patterns, parents give orders and restrictions so that children's learning behavior is forced in learning. While parents use democratic communication patterns, openness between parents and children, so that children's learning behavior is directed and structured, children learn casually, are not burdened and quickly absorb lessons with a study schedule that has been compiled together. Of the three communication patterns above, the effective communication pattern when children study at home during the COVID-19 pandemic is a democratic communication pattern.